The Influence of Career Development and Organizational Culture on Employee Performance (International Journal of Scientific Research and Management (IJSRM), 2018)
The establishment of Bank Pembangunan Daerah is aimed to be the main contributor in the local people’s economic development. Therefore, it is very important to take heed of the company’s performance by evaluating its employees’ performance. Based on the result of interviews and observation, it was found that employee performance was influenced by some factors such as career development and organizational culture. The objective of this research was to examine the influence of career development and organizational culture on employee performance. The research used quantitative approach which involved 242 permanent employees of Bank Pembangunan Daerah. The result of statistic analysis showed that career development and organizational culture had positive and significant influence on employee performance. The implication of this research is expected to be able to help the company’s management increase their employees’ performance by carrying out objective, transparent, and fair career development program and strengthen organizational culture by socializing and monitoring the implementation of firm values.